Mobilidade em potência e discurso publicitário na sociedade contemporânea globalizada: Brasil, 1982-2014 - Nogueira, Maria Alice de Faria (2015)
In the world, today, everything is in motion. People, objects, values, information and images circulate each day more intensively and widely in a social environment which is fluid, connected and risky. When mobility becomes an important element of everyday experience and physical, geographic, virtual or imaginary displacements take front row in the relationships and radically alter the ways of life in all spheres – social, cultural, political and economic – then mobility culture imposes itself and involves everybody in new possibilities and experiences, as well as, in new constraints, risks and discourses that have to be studied. The ever going intense imbrication between mobility culture and advertising discourse constitutes the basis that sustains the thesis and stablishes the two fundamental premises in the study: first, that things in the world reaches the subject regardless of its immobility, by means of objects, information and images that circulate globally; second, that regardless of its commercial, persuasive and selling character, advertising can also be seen as a cultural good that expresses the culture to which it belongs. The articulation of these two premises constitutes the main interest and the object of this research: considering the act of advertising as representation of society, we intend to investigate, within the perspective of the New Mobility Paradigm, how movement is expressed in the advertisement discourse of global brands. The interpretation of global advertisement discourse aims at validating the hypothesis that there is consumption of (im)mobility when the person looks for objects that, depending on their availability (ready-to-hand) and on their potential of use in relation to the environment (affordance), support his everyday (im)mobility, with a certain amount of stability and less risk. The locus of the investigation was Brazil and the study focused its analysis on the 32 years encompassed in the period from 1982 to 2014. Advertisements of brands published in the magazine VEJA during the period of the three FIFA World Cups – 1982 in Spain; 1998 in France, and 2014 in Brazil were analysed.